Improving Food Security Through the Providing of Shoppes for Communities Affected by Covid 19 - Siti Sri Wulandari; Bambang Suratman; Triesninda Pahlevi; Novi Trisnawati (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
This Community Service provides a solution to the above problems, namely by improving nutrition to the community through the provision of basic food ingredients to people affected by COVID-19. The expected benefits of this Community Service are helping the economy, especially to meet the needs of its staples, and the welfare of people affected by COVID-19 in Cemandi Village, Sedati District, Sidoarjo Regency. The method applied is to provide direct food assistance to people affected by COVID-19. The results of the implementation of Community Service in the form of documentation and citizen responses to basic food assistance, among others. The implementation of community service as an effort to increase food security through the provision of basic necessities for the people affected by Covid 19 which was carried out to the residents of Cemandi village, Sidoarjo Regency received a positive response by providing basic necessities from the Community Service team and feeling that it was sufficient for their family's food needs in the next few days and had already right on target because residents desperately need basic food assistance due to decreased income and unable to fulfill their family's nutrition.